“Evaluación de calcio y fósforo en la leche de vaca, y su efecto en la elaboración de queso fresco, en la provincia de bellavista” - Villanueva Díaz, Bautista (2003)
With the objectíve to know contents of calcium and phosphorus intocow' s milk of Brown Swiss and Huallaga in the sector of province of Bellavista, that was collected samples of fresh rnilk and were determined contents of calcium and phosphorus and at once evaluated the effect of them, in the processing and yielding of fresh cheese. For determination of calcium and phosphorus used atomic absorption spectrophotometer and colorimetric method, respectively, during cheese processing evaluated the lactic cultivation and calcium chloride effect, incibation-coagulation time and cheese yield, which utilized the randon completely block statistacal design with factorial arrangement 4*2*4 at 3 repetitions and duncan's and tuckey's comparison tests with P < 0.05 and orthogonal contrasts. The obtained results of this study índícate, calcium contents into nilk. is following form: BMl, BM2, HMl and HM2 are: 919.28, 941.83, 845.42 and 968.72 mg calcium/L milk; thoroughbred Brown Swiss was determined 930.6 mg calcium/L milk, and thoroughbred Huallaga was determined 907 .1 mg calcium/L milk; obtaíning at average 918.9 mg calcium/L milk; and contents of phosphorus was: 1090.15, 605.13, 66633 and 762.25 mg phosphorus/L milk respectively, and aboud races studied were: 847.6 and 714.3 mg phosphorus!L milk; getting a general average 780.95 mg phosphorus/L milk. The incubation-coagu]ation time through addition of 3 % lactic cultivation and 60 g calcium chloride/100 L was 25 min, with a yielding of 151.33 g cheese/L milk; compared when don't add lactic cultivation and calcium chloride, incubation-coagulation time increased until 150 min., and yielding of cheese decreased to 125.30 g chbese/L milk respectively. The physical-chemical analysis on fresh milk was: humidity 87.6%, protein 2.95%, fat 3.9%, ash 0.54% and acídity (lactíc acid) 0.17%; for fresh cheese was: moisture 52.01%, protein 23.76%, fat 21.31%, ash 3.15%, acidity (lactic acid) 0.24%, 913,3 mg calcium and 481. 7 mg phosphorus pergram of fresh cheese, during storage (refrigeration), percentaje of humidity and ash keed on constants. percentage of lactic acid expands to increase. On the determinatíon of mícrobiological activity in fresh cheese, as methylene blue test was 6.5 hours, reduction time, the fresh cheese on study had a microbial recount of. viable aerobian bacteria (3.8x103); recount of S. aureus (l.7x102); recount of coliforms, E. coli, salmonella, mushrooms and yeast ( absence); once passed the storage time by refrígeratíon of fresh cheese on study the microbial recound was: viable aerobian bacteria (4.lxlO\ recound of coliforms (5.2x102), E. coli (2.lxl02), S. aureus (3.lxl02), salmonella, mushrooms and yeast (absence). On sensorial evaluation carried out of fresh cheese on study, compared with a commercial cheese, on attribute flavor was fresh cheese that had major acceptance with 60% acceptability, compared to the commercial cheese with a 40%. Attribute color had not diference, having 50% of acceptance. Attribute odor was 80% acceptobility for fresh cheese, whíle a 20% acceptability for commercial cheese only. Attríbute texture was fresh cheese hada major acceptability 85%, and commercial cheese had 15% acceptability only; moreover the sensorial test after 3 months of storage on refrigeration, was the following: a total of 20 panelists, obtained averages of sensorial attnbites (flavor, color, odor and texture) analyzed, were at ranges from "i like much and i like very much". Oftinun parameters for processing of fresh cheese are: reception, thermic treatment (63ºC/30 min), cooled (35ºC), pre-maturing (3% lactic cultivation), incubation,.coagulation (60 g calcium chloride and 2.5 g curdling/100 L milk), agitation cutting, dewheyed, washed, salted ( 17 g saltfL milk), molded, pressed and exposed to the air.